Determinants of Farmers’ Herbicide Use Decisions: Evidence from Jelekong Village, Baleendah District, Bandung Regency, West Java - Rani Andriani Budi Kusumo; Yayan Sumekar; Anne Charina (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The use of herbicides for weed control is a common practice in rice farming. A variety of factors influences farmers’ decisions to use herbicides. This study aims to analyze the factors affecting farmers' decisions to use herbicides in Jelekong Village, Baleendah District, Bandung Regency. A quantitative research design was employed using a survey technique. The respondents consisted of 115 randomly selected rice farmers. Data were analysed using logistic regression and descriptively through the top two boxes analysis. The results indicate that cost efficiency is the primary factor influencing farmers' decisions to use herbicides. Other significant factors include ease of use, product effectiveness, and the size of the cultivated land. Another key finding is that informal social networks among farmers play a substantial role in the decision-making process, outweighing the influence of extension agents or promotional efforts from herbicide producers. These findings contribute theoretically by reinforcing the importance of socio-economic variables, particularly in farmers' decisions to use herbicides.  In practice, this finding highlights the need for policy interventions that prioritize community-based extension strategies as an effective means of disseminating knowledge about herbicide use. These strategies must be integrated into farmers' social networks and tailored to their socioeconomic conditions and access to information because these factors significantly impact their decisions about herbicide use.